Delayed presentation of cannabis induced pancreatitis. Issue 3 (17th March 2022) - Song, David; Geetha, Harinivaas Shanmugavel; Jain, Samkit; Reyes, Jonathan Vincent; Jaiswal, Vikash; Nepal, Gaurav; Lieber, Joseph
Abstract: A thorough history and identifying risk factors are pivotal in establishing the cause of pancreatitis and preventing recurrences to curb the incidence of chronic pancreatitis and/or pancreatic cancer. Abstract : A thorough history and identifying risk factors are pivotal in establishing the cause of pancreatitis and preventing recurrences to curb the incidence of chronic pancreatitis and/or pancreatic cancer.